Simulating the Impact of COVID-19 on Formal Firms in Eswatini - Lees, Adrienne; Mascagni, Giulia; Santoro, Fabrizio (World Bank, Washington, DC, 2020)
Prior to COVID-19, Eswatini faced numerous developmental challenges with stagnating poverty and economic growth. Lockdown measures wereintroduced from 17 March, including schools closures, limitations on public and private gatherings, the suspension of non-essential travel within cities, and border closures. Economic activity has been damaged further by South Africa’s strict containment measures and the closure of some portsof entry with South Africa.